2015
DOI: 10.5539/gjhs.v8n2p288
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Pattern of Antibiotics in Patient Underwent Open Heart Surgery With Nosocomial Infection in North of Iran

Abstract: Background:Patients who undergo cardiac surgery appear to be at increased risk for the development of Nosocomial infections (NIs). The development of antibiotic-resistant infections has been associated with significantly greater hospital mortality rates compared to similar infections caused by antibiotic-sensitive pathogens.Objectives:The purpose of this study is survey of Nis and antibiotic resistance patterns of causative bacteria among patients who underwent open heart surgery in the north of Iran during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
(39 reference statements)
1
20
2
3
Order By: Relevance
“…* indicate significant differences Table 3; SSI, surgical site infections. NHSN rates were based on the two published NHSN reports (references [13,14]). NHSN VRE rate shown was the rate of both Enterococcus faecalis and Enterococcus faecium combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…* indicate significant differences Table 3; SSI, surgical site infections. NHSN rates were based on the two published NHSN reports (references [13,14]). NHSN VRE rate shown was the rate of both Enterococcus faecalis and Enterococcus faecium combined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data on surgery-specific pathogens in these reports were absolutely lacking or retrieved from a small number of patients [10][11][12]. Likewise, very limited data on the resistance patterns of pathogens causing SSI were reported in the Gulf Cooperation Council (GCC) [10] and the Middle Eastern countries [13,14]. For example, a study that combined aggregate SSI data from 30 developing countries (including some regional ones) could not present data on pathogen profile nor bacterial resistance [15].…”
Section: Introductionmentioning
confidence: 99%
“…The ESBL-producing isolates' outbreak in hospitals is related to different risk factors such as use of antimicrobials and indwelling catheters (urinary catheters and tracheal tubes) and person-to-person transmission, and since these genes are located on plasmids, they can easily spread in hospital environments. Different studies have reported the need for more precaution in use of antibiotics and the contorting rate of antibiotic resistance in ICU and neonatal care units (14)(15)(16). Varkey et al in India reported that out of 361 isolated bacteria from blood samples, including E. coli, K. pneumoniae and E. cloacae, 250 isolates were found to be ESBLs-producing organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Kardiyak cerrahi sonrasında gelişen SBİE'lar da; uzayan hastane yatışının, maliyet artışının ve mortalitenin önemli bir nedeni olarak karşımıza çıkmaktadır 1 . Literatürde bu enfeksiyonların sıklığı %2,25-24,9 arasında bildirilmektedir [1][2][3][4][5][6][7] .Kalp ameliyatları sonrası, SBİE gelişme riskini artıran en önemli neden; kardiyopulmoner "by-pass" ve ekstrakorporeal dolaşıma bağlı artan stress faktörlerinin genel bir inflamatuvar yanıt oluşturmasıdır. Bazı durumlarda bu inflamatuvar yanıtın abartılı bir durumda meydana gelmesi, sistemik inflamatuvar yanıt sendromuna ve çoklu organ disfonksiyonuna yol açabilmektedir.…”
Section: Introductionunclassified
“…Bazı durumlarda bu inflamatuvar yanıtın abartılı bir durumda meydana gelmesi, sistemik inflamatuvar yanıt sendromuna ve çoklu organ disfonksiyonuna yol açabilmektedir. Ayrıca; birden fazla cerrahi insizyon bölgesinin bulunması, ameliyat süresinin uzunluğu, postoperatif dönemde invazif araçların sıklıkla kullanılması ve yine bu dönemde hastane personeli ile temasın fazla olması, inflamasyonenfeksiyon ayırımındaki klinik zorluklar nedeni ile bazen geniş endikasyonla antibiyotik kullanımı, ameliyat yapılan hasta grubunda ileri yaş, komorbidite ve kompleks cerrahi girişimlerin olması SBİE'ların artması ile ilgili diğer risk faktörleri olarak sıralanabilir 8 Literatürde kardiyak cerrahi sonrası görülen SBİE'lar arasında en sık (%32,9-52,6) rastlanan enfeksiyon türü genellikle CAE'larıdır ve hızı %2-10 arasındadır 1,3,4,6,12,17,18 . Cerrahi alan enfeksiyonları artmış morbidite, mortalite, uzayan hastane yatışı ve artan maliyet ile beraber istenmeyen komplikasyonlardandır [19][20][21] .…”
Section: Introductionunclassified